The Quality of Official Services for the Leadership Administration (TUP) in the General Section of Kotamobagu City Regional Secretariat - Suhartien Tegela,; Thelma Wawointana,; Laurens Bulo, (Technium Social Sciences Journal, 2025)
This study aims to analyze the quality of official services of the Subdivision of Leadership Administration (TUP) of the General Section of the Kotamobagu City Regional Secretariat in administrative services for preparing the Mayor's work agenda. The assessment is carried out based on five dimensions of public service quality, namely tangible (physical evidence), reliability, responsiveness, assurance, and empathy. The research method used is qualitative with an interview, observation, and documentation approach. The results showed that the quality of service in the tangible dimension needs to be improved, especially related to physical facilities such as work tools and room renovations. In the reliability dimension, services have run according to the SOP, but are constrained by limited information technology and cross-agency coordination. Staff responsiveness is quite good, but additional staff are needed to handle the high workload. The assurance dimension shows the trust and professionalism of staff who are good enough to maintain confidentiality and smooth the work agenda. In the empathy dimension, staff attention to the needs of leaders and stakeholders is considered adequate, but communication with guests or service users can be further improved. The services of the Administration Subdivision of the General Secretariat of Kotamobagu City are quite good, but still require improvement in terms of facilities, information technology, and strengthening human resources including improving facilities and infrastructure, implementing information technology, adding staff, and strengthening coordination and communication to support more effective and efficient services.